Uji Aktivitas Antibakteri Krim Ekstrak Bunga Kecombrang (Etlingera elatior) dengan Basis Minyak Sawit terhadap Bakteri Penyebab Inflamasi pada Kulit - Dewi Yuliana Putri (Fakultas Farmasi Universitas Jember, 2025)
Skin inflammation is a common disease often caused by bacterial infections. Bacteria that can cause skin infections include Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. The kecombrang flower (Etlingera elatior) is one of the herbal plants with potential antibacterial properties. This study aims to determine the antibacterial activity of kecombrang flower methanol extract cream at concentrations of 1%, 2%, and 4% with a HAMIN® base against bacteria causing skin inflammation, namely Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. The study began with the extraction of kecombrang flowers using methanol solvent through the maceration method. The obtained thick extract was then formulated into cream preparations at concentrations of 1%, 2%, and 4%, followed by evaluation of the cream to determine the effect of extract concentration variations on the physical and chemical properties of the cream. The study continued with antibacterial testing of the cream using the disk diffusion method. Antibacterial activity testing revealed that kecombrang flower extract cream at concentrations of 2% and 4% exhibited antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa, with increasing extract concentrations resulting in stronger activity. However, no antibacterial activity was observed against Escherichia coli at any concentration. The average inhibition zone diameters formed by the cream at 2% and 4% concentrations were 7.7 ± 0.33 mm and 11.32 ± 1.08 mm for Staphylococcus aureus, while for Pseudomonas aeruginosa were 8.04 ± 0.78 mm and 9.06 ± 0.32 mm.
Reuploud file repoitori 15 Apr 2026_Firli_Tata
Keywords: Kecombrang flower; Cream; HAMIN®; Antibacterial activity